The Reality of Using Co-Curricular Model-Based Teaching Strategies Activities by the Teachers of Physics with its Practice Specifications - Al-Omary, Wesal (Jordan Journal of Educational Sciences, 2015)
This study aimed at exploring the reality of using co-curricular model-based teaching strategies activities by the teachers of physics along with its practice specifications. Such usage was investigated as being verified in light of gender, teaching experience, and scientific qualifications of the teachers understudy. The sample consisted of 74 physics male and female teachers in the Directorate of Education in Irbid, in the second semester of the academic year 2013/2014. Descriptive analytical method was used. A scale of educational activities was developed. The scale consisted of 25 statements which had acceptable measures of validity and reliability for the purposes of this study. The study results showed that the reality of using co-curricular teaching activities was reported as medium, with statistically significant differences (α= 0.05) in the actual use of activities due to the variable of gender in favor of female teachers, yet no statistically significant (α= 0.05) differences were found in the actual use of activities due to the variable of the teaching experience. The results also reported statistical significant differences (α= 0.05) in the actual use of activities due to the variable of the scientific qualifications in favor of the postgraduates level.